Coherent optomechanical state transfer between disparate mechanical resonators. Issue 1 (December 2017) - Weaver, Matthew; Buters, Frank; Luna, Fernando; Eerkens, Hedwig; Heeck, Kier; Man, Sven; Bouwmeester, Dirk
Abstract Systems of coupled mechanical resonators are useful for quantum information processing and fundamental tests of physics. Direct coupling is only possible with resonators of very similar frequency, but by using an intermediary optical mode, non-degenerate modes can interact and be independently controlled in a single optical cavity. Here we demonstrate coherent optomechanical state swapping between two spatially and frequency separated resonators with a mass ratio of 4. We find that, by using two laser beams far detuned from an optical cavity resonance, efficient state transfer is possible. Although the demonstration is classical, the same technique can be used to generate entanglement between oscillators in the quantum regime. Coupled mechanical resonators where each mode can be separately controlled are a promising system for quantum information processing. Here, Weaver et al. demonstrate coherent swapping of optomechanical states between two separate resonators.